Body social models of disability: Examining enactive and ecological approaches - Jurgens, Alan (Frontiers in Psychology, 2023)
Autistic philosopher and neurodiversity proponent Robert Chapman (2021) argues that disability may be best understood by utilizing an ecological functional model where the focus is on the intersection and overlaps between relational contributions to collectives and group functioning with individual functionality. This presents an alternative to both social-relational models of disability advocated by other neurodiversity proponents and the orthodox medical model of disability. While enactivists such as Michelle Maiese and Juan Toro, Julian Kiverstein and Erik Rietveld have also offered relational models of disability that challenge the orthodox medical model, I argue that unlike the ecological functional model, these enactivist models remain problematically committed to an individualist methodology. Drawing on what Miriam Kyselo has labeled the body social problem, I show that the enactivist models not only face theoretical issues, but also practical issues in terms of their recommended intervention strategies for disability. I argue that for these reasons, if enactivists want a relational model of disability, then they should adopt both a neurodiversity paradigm approach and Chapman’s ecological functional model.